The characteristics of systems which are nearly in a state of neutral static stability - Duncan, W. J. (College of Aeronautics, Cranfield, 1950)
It is shown that the rate of subsidence or divergence ﮑ of a system which is near a state of neutral static stability can easily be calculated for knowledge of the mode of displacement in the neutral state and this model is found by solving a set of linear algebraic equations. The first order correction to the mode can also be found and in important cases this can be made the basis for calculating a second approximation to ﮑ; if necessary a further correction to the mode can now be found from this a still more accurate root can be calculated. The method can be extended to continuous systems having infinitely many degrees of freedom.